2005
DOI: 10.1073/pnas.0505587102
|View full text |Cite
|
Sign up to set email alerts
|

An improved reverse genetics system for influenza A virus generation and its implications for vaccine production

Abstract: The generation of vaccines for highly pathogenic avian influenza viruses, including those of the H5N1 subtype, relies on reverse genetics, which allows the production of influenza viruses from cloned cDNA. In the future, reverse genetics will likely be the method of choice for the generation of conventional influenza vaccine strains because gene reassortment by more traditional methods is cumbersome. Established systems for the artificial generation of influenza A viruses require transfection of cells with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 24 publications
1
116
0
1
Order By: Relevance
“…Reverse genetics systems, developed in the 1990s, still remain a challenging and promising technology, enabling the creation of influenza viruses with modified replicative, pathogenic, antigenic, and immunogenic properties (20,42). We and others have recently shown that it is possible to generate replication-deficient and thus safe, but still highly immunogenic, influenza A viruses by genetic engineering of the NS gene segment (15,18,32,48,51,61).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse genetics systems, developed in the 1990s, still remain a challenging and promising technology, enabling the creation of influenza viruses with modified replicative, pathogenic, antigenic, and immunogenic properties (20,42). We and others have recently shown that it is possible to generate replication-deficient and thus safe, but still highly immunogenic, influenza A viruses by genetic engineering of the NS gene segment (15,18,32,48,51,61).…”
Section: Discussionmentioning
confidence: 99%
“…The HA mutants A/WSN/33 HA-MAY and A/WSN/33 HA-MAC were created. The pTM and pC plasmids required for reverse genetics were transfected into 293T cells according to a published protocol (45). After 48 h of transfection, cytopathic effects were monitored, and hemagglutinin assays were performed to confirm the presence of viruses.…”
Section: Methodsmentioning
confidence: 99%
“…HA (A/Aichi/2/68) and NA (A/Singapore/1/57) DNA sequences cloned into eukaryotic expression vector pCAGGS (58) (45). A QuikChange II XL site-directed mutagenesis kit (Agilent) was used to create site-directed mutations in three acylation sites of influenza virus hemagglutinin (Cys 555, Cys 562, and Cys 565) located in the protein C terminus.…”
Section: Methodsmentioning
confidence: 99%
“…Another type of influenza vaccine is the cold-adapted live influenza virus vaccine (CAIV) which has been shown to be more immunogenic than TIV in inducing protective immunity and may be associated with a longer-lasting and more cross-protective immune response than is elicited by TIV [5]. A new technology termed 'reverse genetics' has been developed to generate high growth reassortants [6][7][8][9][10][11] and combines viral genes from the high growth yield laboratory strain of influenza A virus A/PR/8/34 (H1N1) with genes encoding protective antigens of the target viral strains [12]. However, this technology does not change the subsequent manufacturing process needed to produce large stocks of vaccine viruses to make the final TIV or CAIV formulations.…”
Section: Introductionmentioning
confidence: 99%